Asuransi Islami Dan Pembangunan Ekonomi Umat - Muhammad Iswadi (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2015)
This paper discusses the debate jurists of insurance, there are some that allow and prohibit, with various arguments. At the next turn spawned Takaful is a concrete solution to address the issue of people who really need insurance. Islamic insurance does have differences in terms of both form and nature with conventional insurance. There are two types of takaful insurance products, namely family takaful and general takaful. This insurance can also increase or help the economic development of the people, with a range of multiplier effect caused